Legal Protection for Consumers Against Losses Due to The Provision of Counterfeit Money by Non-Bank Money Changers - Ni Komang Trisna Desinta; I Nyoman Putu Budiartha; I Made Aditya Mantara Putra (Warmadewa Press, 2024)
The growth of tourism has encouraged the development of non-bank money changers. However, there are non-bank money changer practices without a business license, which allows the circulation of counterfeit currency to consumers. Due to the absence of rules regarding the legal certainty of consumers related to the liability of businesses for the loss of consumers who obtain counterfeit money. The formulation of this research problem, namely: 1) How is the regulation of legal protection for consumers in non-bank money changer activities? 2) How is the liability of business actors money changer non-bank for the loss of consumers who get counterfeit money from the exchange of foreign currency?. The research method used is normative legal research with a statutory approach and conceptual approach. The results showed that the regulation of non-bank money changer only based on Bank Indonesia Regulation No. 18/20/PBI/2016. If consumers suffer losses due to counterfeit money, then consumers can request compensation in accordance with Article 19 of the GCPL and if the business refuses to provide accountability, consumers can claim their losses by suing the business according to Article 1365 and 1366 of the Civil Code.